Assessing the environmental impact of logistics sites through CO2eq footprint computation - Perotti, Sara; Prataviera, Lorenzo Bruno (Wiley, 2022)
The environmental sustainability of logistics facilities is widely acknowledged as an important issue, but a comprehensive standardised methodology for assessing their environmental impact is lacking. This study proposes a structured model for quantifying both consumptions and generated greenhouse gas (GHG) emissions, adopting a three-phase methodology that combines multiple methods. A literature-based conceptual framework was leveraged to design an analytical model, and in-depth interviews with 11 senior logistics managers were conducted. The study offers a replicable methodology that considers heterogeneous sources of consumption and related end-use types, further splitting consumptions and emissions by warehouses' functional areas. It offers a set of Environmental Performance Indicators (EPIs) that could bolster a clearer understanding of the warehouse environmental performance. A robust tool is offered to managers to support their decision-making processes, allowing for both internal assessments and benchmarking with competitors or other players along the supply chain, thus contributing to shape company's, or even supply chain, sustainability strategies.
Keywords: carbon footprint; environmental sustainability; green warehousing; logistics; sustainability strategy